1997
DOI: 10.1111/j.1600-0420.1997.tb00157.x
|View full text |Cite
|
Sign up to set email alerts
|

Congenital aphakia in Peters' anomaly syndrome

Abstract: ABSTRACT.The authors report a case of congenital bilateral corneal opacities in which one of the eyes was enucleated because of malignant glaucoma and corneal perforation. Corneal defects and iridocorneal adhesion were found, but aphakia was the major pathologic ocular finding. The clinical picture and pathology study indicated this case as a Peters' anomaly presenting congenital aphakia. eters' anomaly is a congenital disease P that affects mainly the posterior cornea (Alkemade 1969). It is most often bilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
6
0
1

Year Published

2000
2000
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…Both patients in this study showed corneal opacification, ectasia, and vascularization. In addition, our first patient had a dislocated crystalline lenses and the second patient had had congenital aphakia, both of which have been described with Peters anomaly and congenital anterior staphylomas 9,10…”
Section: Discussionmentioning
confidence: 84%
“…Both patients in this study showed corneal opacification, ectasia, and vascularization. In addition, our first patient had a dislocated crystalline lenses and the second patient had had congenital aphakia, both of which have been described with Peters anomaly and congenital anterior staphylomas 9,10…”
Section: Discussionmentioning
confidence: 84%
“…It is important to evaluate the status of lens as many corneal opacities may have an absent lens, a condition known as congenital primary aphakia. [ 1 2 ]…”
mentioning
confidence: 99%
“…ASD resulting from the abnormal development of neural crest cells encompasses a broad range of ocular malformations classified in detail by its characteristics in human ophthalmology [ 8 , 21 ]. It includes CAS, PA and aphakia, although it is sometimes presents complications [ 6 , 11 , 18 , 19 , 23 ]. ASD is also well known in animals [ 2 , 7 ].…”
mentioning
confidence: 99%